Three Nutritional Indices Are Effective Predictors of Mortality in Patients With Type 2 Diabetes and Foot Ulcers - Hong, Jing; Huang, Qi-Qi; Liu, Wen-Yue; Hu, Xiang; Jiang, Fei-Fei; Xu, Ze-Ru; Shen, Fei-Xia; Zhu, Hong (Frontiers in Nutrition, 2022)
Introduction: Malnutrition has been associated with mortality in various diseases. This retrospective cohort study aimed to investigate the relationship between three nutritional indices and all-cause mortality in patients with diabetic foot ulcers (DFUs). Materials and Methods: A total of 771 patients diagnosed with DFUs in the First Affiliated Hospital of Wenzhou Medical University from 2015 to 2019 were included in this retrospective cohort study. Patients were classified as high nutritional risk groups or low nutritional risk groups according to the optimal cut-off values of the geriatric nutritional risk index (GNRI), prognostic nutritional index (PNI), and controlling nutritional status (CONUT), respectively. The associations of three nutritional indices with all-cause mortality were evaluated by multivariable Cox regression analyses. Results: Log-rank tests indicated that patients with high nutritional risk had lower overall survival rates (all p<0.001). The multivariable Cox regression revealed that low GNRI (adjusted HR 2.01, 95%CI: 1.37-2.96, P < 0.001), low PNI (adjusted HR 2.04, 95%CI: 1.29-3.23, P = 0.002) and high CONUT (adjusted HRs 1.54, 95% CI: 1.07-2.23, P = 0.021) were independently associated with high all-cause mortality. In subgroup analyses, only GNRI predicted higher all-cause mortality in patients with severe DFUs, while all of the three indices persisted as independent prognostic factors in patients with no severe DFUs. Discussion: The present study demonstrated that three nutritional indices were effective predictors of all-cause mortality in patients with DFUs. Routine screening for malnutrition using any of the three nutritional indices might be a simple and effective way to identify high-risk patients with DFUs. GNRI can be used as an independent prognostic indicator in patients with severe DFUs.